Theology in Malaysia : Between the Mainstream and the Periphery - Malik, Maszlee (Kalam Verlag für islamische Theologie und Religionspädagogik KG, 2013)
This paper explores the clash of the theologies in modern Malaysia by examining the history of Islamic theology in the country